Management of Patients With Acute Cholecystitis After Percutaneous Cholecystostomy: From the Acute Stage to Definitive Surgical Treatment - Hung, Yu-Liang; Sung, Chang-Mu; Fu, Chih-Yuan; Liao, Chien-Hung; Wang, Shang-Yu; Hsu, Jun-Te; Yeh, Ta-Sen; Yeh, Chun-Nan; Jan, Yi-Yin (Frontiers in Surgery, 2021)
Percutaneous cholecystostomy (PC) has become an important procedure for the treatment of acute cholecystitis (AC). PC is currently applied for patients who cannot undergo immediate laparoscopic cholecystectomy. However, the management following PC has not been well reviewed. The efficacy of PC tubes has already been indicated, and compared to complications of other invasive biliary procedures, complications related to PC are rare. Following the resolution of AC, patients who can tolerate anesthesia and the surgical risk should undergo interval cholecystectomy to reduce the recurrence of biliary events. For patients unfit for surgery, whether owing to comorbidities, anesthesia risks, or surgical risks, expectant management may be applied; however, a high incidence of recurrence has been noted. In addition, several interesting issues, such as the indications for cholangiography via the PC tube, removal or maintenance of the PC catheter before definitive treatment, and timing of elective surgery, are all discussed in this review, and a relevant decision-making flowchart is proposed. PC is an effective and safe intervention, whether as expectant treatment or bridge therapy to definitive surgery. High-level evidence of post-PC care is still necessary to modify current practices.